Solution processed low-voltage organic transistors based on self-assembled monolayer gate dielectrics - Ball,JM; Wöbkenberg,PH; Colléaux,F; Smith,J; Bradley,DDC; Anthopoulos,TD (2009)
Reduction in the operating voltage of organic field-effect transistors (OFETs) is sought for their successful implementation into future portable and low-power electronic applications. Here we demonstrate OFETs with operation below 2 V enabled by the use of self-assembled monolayer (SAM) gate dielectrics with high geometrical capacitances. A high surface energy monolayer is chosen to allow processing of small molecule semiconductors from solution. Impedance spectroscopy measurements of metal-insulator-semiconductor devices suggest the geometrical capacitance of the alumina-SAM dielectric can reach ∼1 μF/cm2 when accumulating charge at the semiconductor-insulator interface. Atomic force microscopy images reveal that the glass substrates and the SAM-functionalized aluminum gate electrode display significant roughness. Despite this, mobilities of 0.02 cm2/Vs are demonstrated. These results represent an important step towards low-power solution processable electronics. © 2009 SPIE.